Prokrastinasi Akademik dalam Pergaulan Mahasiswa PGSD - Nugroho, Femas Anggit Wahyu; Ningsih, Nur Marisa Supriyanti; Az-Zahrah, Sagita Shofa; Fajrie, Nur (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 24 No 1 (2024), 2024)
This study aims to find out more about the behavior of academic procrastination in the association of PGSD students. The subjects of this study were 7 semester 4 PGSD students at Muria Kudus University who had experienced academic procrastination and had a social environment that encouraged them to do so. The research method uses qualitative methods with a case study approach. Data collection is done through observation, in-depth interviews, documentation, and recording. Data validity test includes internal validity, external validity, reliability, and objectivity. Data analysis techniques include the stages of collecting, reducing, presenting, and drawing conclusions. The results of the study indicate that there are interrelated internal and external factors that cause academic procrastination behavior. Internal factors in the form of physical and psychological conditions. External factors include lack of support and cooperation, busy working and organizing, and social influences. Social influence is the most dominant external factor causing academic procrastination. The influence of association triggers the emergence of academic procrastination behavior due to self-alignment efforts to be accepted in a group characterized by cohesiveness, agreement, and obedience.